Specific features of correlation between the syntactical stylistic devices and their evaluative meanings in English media genres - Glazko, Pavel P. (Journal of the Belarusian State University. Philology, 2023)
The given paper attempts to elucidate the correlation between syntactical stylistic (expressive) devices and their contextual evaluative meanings in the genres of blog and column of the USA media space. The categories of expressiveness and evaluativity are crucial for mindful and responsible consumption of modern media content produced in the conditions of increasing subjectivity. The research is based on the analysis of 200 texts (100 texts per genre) recently published by different authors on their personal websites as well as official websites of newspapers during the 2020–2023. The results of linguo-stylistic, contextual, and quantitative analyses attest to some similarities as well as a number of differences in the expressive and evaluative organisation of the genres in question. In columns syntactical stylistic devices tend to augment the negative evaluative meaning which testifies to the critical nature of this genre. Unlike the column, the genre of blog is characterised by balancing the use of syntactical means which amplify the negative evaluation with those which intensify the negative evaluation. In particular, the positive evaluative meaning correlates with the expressive means of dialogisation, while the negative evaluation is associated with the syntactical devices of accentuation.